REDESCUBRIMIENTO DE UNA ESPECIE DE CALCEOLARIA (CALCEOLARIACEAE) - Muñoz-Schick, Mélica; Moreira-Muñoz, Andrés (Gayana Botánica, 2008)
The species Calceolaria reicheana, nomen nudum, was rediscovered in the Metropolitan Region, Chile. It is considered as a valid species, described and renamed as Calceolaria espinosae. A new locality is also recorded.